2018
DOI: 10.3136/fstr.24.747
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Acetic, Citric and Lactic Acid in the Cassava Starch Modification on Physical, Rheological, Thermal and Microstructural Properties

Abstract: Effects of acid modification on the physicochemical, rheological, microstructural and expansion on cassava starch with lactic, acetic and citric acids in proportions of 5 %, 10 % and 15 % were investigated. This effect was verified on swelling power and solubility index, rheology, pH, scanning electron microscopy, thermal analysis and baking test. The results were available by ANOVA and Tukey test. The study indicates that the acid treatment influenced significantly the physicochemical properties. The lactic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…Furthermore, the peak viscosity of PAW-WF was the lowest. It may be due to the hydrolysis of starch chains by the acidic components in the PAW, resulting in a decrease in the viscosity of WF ( 29 ). On the other hand, the acidic components in PAW also hydrolyzed the protein, resulting in a lack of protein network formation, which increases the brittleness of swollen starch granules, resulting in a decrease in viscosity of WF ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the peak viscosity of PAW-WF was the lowest. It may be due to the hydrolysis of starch chains by the acidic components in the PAW, resulting in a decrease in the viscosity of WF ( 29 ). On the other hand, the acidic components in PAW also hydrolyzed the protein, resulting in a lack of protein network formation, which increases the brittleness of swollen starch granules, resulting in a decrease in viscosity of WF ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…This could be related to the attack of the kernel coat structure by the active substances produced by low-temperature plasma treatment and oxidation, which decreases the flatness of the grain surface and alters the kernel coat surface (Liu et al, 2022). Compared with native starch, PEF-treated starch has lower contents of slowly digestible resistant starch (Zeng et al, 2016). During MW baking, rapid heat transfer occurs from the inside to the surface of the food.…”
Section: Current Challenges and Future Research Directionsmentioning
confidence: 99%
“…Moreover, the PEF-processed starch is quickly gelatinized owing to the massive rearrangement and destruction of its molecular structure during high-field strength PEF application. After PEF treatment, structural changes in waxy rice starch affect the digestibility pattern, thus increasing the content of rapidly digestible starch (RDS), while decreasing the content of slowly digestible starch (SDS) compared with that in native starch (Zeng et al, 2016). Similarly, another study revealed that increasing the electric field intensity significantly increased the RDS but decreased the SDS of pea starch (Li, Wu, et al, 2019).…”
Section: Pef Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, compared with DW-ANN, PAW-ANN resulted in a lower peak viscosity. The decrease of viscosity could be because the starch chains were largely affected by acid hydrolysis, which generated fragmentation of starch chains (26).…”
Section: Pasting Propertiesmentioning
confidence: 99%